Surface Dependent Inhibition of Mycobacterium abscessus by Diverse Pseudomonas aeruginosa Strains - Ayantu W. Idosa; Daniel J. Wozniak; Luanne Hall-Stoodley (Microbiology Spectrum, 2022)
ABSTRACT Both Pseudomonas aeruginosa and Mycobacterium abscessus are bacteria that cause pulmonary infection in people with inflammatory lung disease, including individuals with cystic fibrosis (CF). These bacterial species inhabit the same environmental reservoirs (soil and water) and can be coisolated in the lungs of people with CF. We investigated the interaction of these bacteria and found an antagonistic interaction favoring P. aeruginosa that was observed in biofilms but not in planktonic cultures. This antagonism extended to multiple P. aeruginosa strains and against Mycobacterium smegmatis. We tested known P. aeruginosa mutants for genes that can play roles in interbacterial contact-dependent (type III and type VI secretion systems) and contact-independent (quorum sensing, type II secretion) antagonism pathways to interrogate the mechanism of action. Our results indicate that well-known mechanisms of interbacterial competition are not responsible for the antagonism of P. aeruginosa toward M. abscessus, suggesting a novel antibacterial strategy. IMPORTANCE The biofilm lifestyle is favored by many organisms, and understanding interbacterial interactions that occur between coisolated bacterial species can provide new information regarding bacterial defense mechanisms and antibacterial targets. This may also provide insights into possible interbacterial interactions impacting host immunity during coinfection. Here, we investigate an antagonistic interaction favoring P. aeruginosa over M. abscessus exclusively in dual-species biofilms and not in liquid coculture.